The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10096-018-3335-2
|View full text |Cite
|
Sign up to set email alerts
|

Repeated antifungal use audits are essential for selecting the targets for intervention in antifungal stewardship

Abstract: A previous audit to assess the quality of antifungal use was performed in our hospital in 2011. After 5 years of antifungal stewardship program (AFS), we performed a follow-up audit in order to describe the long-term effect of such program. Using a predefined score, we evaluated the antifungal use in 100 consecutive adult inpatients receiving systemic antifungals. Results of the present audit were compared with those of a previous one, performed in 2011, before the implementation of our AFS. After 5 years, AFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…glabrata to micafungin is similar to the alarming data of echinocandins resistance reported by other authors [26, 36]. Our results could represent a warning, suggesting the need of performing a prospective azole and echinocandins resistance surveillance in our country, reviewing the antifungal prophylaxis policies and implementing a national antifungal stewardship program before reaching a critical level of resistance [37, 38].…”
Section: Discussionsupporting
confidence: 87%
“…glabrata to micafungin is similar to the alarming data of echinocandins resistance reported by other authors [26, 36]. Our results could represent a warning, suggesting the need of performing a prospective azole and echinocandins resistance surveillance in our country, reviewing the antifungal prophylaxis policies and implementing a national antifungal stewardship program before reaching a critical level of resistance [37, 38].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, adherence to guidelines in terms of dosing of antifungal drugs and duration of therapies significantly improved after our AFS intervention, while no differences were found by some other studies. Indeed, Lachenmayr et al, 4 in a German Department of Hematology and Oncology, found no significant improvement in duration of antifungal treatment (but an increase in dosage accuracy), and Valerio et al 21 carried out a follow‐up audit after 5 years of an AFSp, with no significant improvement regarding adequacy of dosing and the length of therapy. Minimising potential complications by optimising both dosing and duration is one of the goals of an AFS, and our implementation proved to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although gathering baseline data is of paramount importance for defining prescribing trends and identifying areas of improvement, 109 none of the aforementioned studies assessed the prescribing quality of antifungals in terms of indications, dosage or length of treatment. 36 Accordingly, it is not possible to evaluate what proportion of COVID-19 patients have been given antifungal treatment deemed unnecessary.…”
Section: Antifungal Utilization In Covid-19 Patientsmentioning
confidence: 99%
“…As for treatment, voriconazole currently represents the first-line treatment for IPA. 102 , 110 , 111 However, there are many drawbacks associated with voriconazole treatment including major drug–drug interactions, 109 the requirement for therapeutic drug monitoring 117 and the limited spectrum of activity. Although there are few data outside the haematological setting, isavuconazole goes beyond these limits, offering a wider spectrum of antifungal activity than voriconazole, fewer toxicities and fewer drug–drug interactions as well as a lack of cyclodextrin, which is a solubilizing agent used in some other azoles (e.g.…”
Section: Improving Afs Of Fungal Infections In Patients With Covid-19mentioning
confidence: 99%